Research on the Reverse Technology Spillover Effect from China’s CVC Overseas Investments - Xiaoli Wang; Yi Tan (International Journal of Financial Studies)
China’s corporate venture capital (CVC) overseas investment began in the late 20th century and has expanded significantly over the years. By 2021, more than 265 Chinese institutions and companies had engaged in cross-border investments, contributing over USD 100 billion. These investments present a unique opportunity to examine the reverse technology spillover effect on China’s technological development. Using a Difference-in-Differences model and regression analysis, we investigate whether China’s CVC overseas investments drive technological progress. Our findings reveal three key insights: (1) these investments have a positive impact on China’s technological advancement, (2) the effect is stronger when the host country has a higher level of technology, and (3) larger investment amounts amplify the impact. This research not only highlights the transformative potential of cross-border CVC investments but also demonstrates how enterprises can leverage reverse innovation spillovers to accelerate China’s technological progress. Additionally, we introduce a novel approach to studying this phenomenon, contributing to the existing scholarship on global innovation dynamics.